Kemampuan Menulis Puisi Siswa Kelas X SMA Negeri 7 Kota Bengkulu - Afifah, Afifah; Yulistio, Didi; Kurniawan, Rio (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Research objectives know the poetry writing skills of first-grade students of SMA Negeri 7 Bengkulu city. This research uses descriptive methods with quantitative approaches. The population in this study was all first-grade students of SMA Negeri 7 Bengkulu city with 425 students in total. Samples in this study used simple random sampling as much as 15% of 63 population. Data collection technique is a documentation technique with test result of writing student poems that have become documents archived by the teacher. The ability to write poetry is judged on five aspects, namely the accuracy of the content with the title, the choice of words, the use of majas and symbolism, the utilization of verification (rhyme and rhythm), and typography. The data analysis technique used is a simple statistic by calculating the average value. The results of this study showed that the average ability in write poetry first-grade students SMA Negeri 7 Bengkulu city is 58.30 with enough category. The average ability to write student poems based on the accuracy aspect of the content and title is 16.33 with good categories, the average ability to write student poems based on the aspect of word choice is 14.20 with enough categories, the average ability to write student poems based on aspects of majas use and symbolism is 10.63 with enough categories, the average ability to write student poetry based on aspects of verification utilization (rhyme and rhythm) is 9.40 with enough category , the average ability to write student poetry based on typographic aspects is 7.87 with enough categories.